Quantum chemical calculations on the mechanism and kinetics of ozone-initiated removal of p-coumaryl alcohol in the atmosphere. (August 2020) - Sun, Yanhui; Chen, Xiaoxiao; Xu, Fei; Wang, Xiaotong
Abstract: p -Coumaryl alcohol ( p -CMA), as the simplest lignin precursor, was determined in the process of lignin polymer degradation and wood smoke. However, its transformation and migration in the atmosphere have not been well clarified. In this work, the gas-phase reaction mechanisms and kinetic parameters of ozone-initiated removal of p -CMA were performed by using quantum chemical calculations. Seven primary addition reaction pathways were summarized. A more comprehensive and detailed reaction routes of the favorable Criegee intermediate (IM9) were presented, including the reactions with small molecules, as well as its own isomerization and decomposition reactions. p -Hydroxybenzaldehyde (P1) is the most dominant product in the further reactions of IM9 and the subsequent ozonolysis mechanisms of P1 also were elucidated. All thermodynamic calculations were investigated on the density functional theory (DFT) method at the M06–2X/6-311 + G (3df, 2p)//M06–2X/6-311 + G (d, p) level. The overall and individual rate constants have estimated by using the KiSThelP under typical atmospheric temperature (198–338 K) and pressure. The total rate constant is 3.37 × 10 −16 cm 3 molecule −1 s −1 at 298 K and 1 atm. In addition, the atmospheric lifetime of p -CMA by ozone-determined is 1.18 h under the average ozone concentration of 7 × 10 11 molecules cm −3 . The short lifetime indicates that the degradation processes of p -CMA determined by O3 cannot be ignored, especially in areas where the tip concentration of O3 molecules is high. The present study provides a synthetical investigation on ozonolysis of p -CMA for the first time and enriches our understanding of atmospheric oxidation processes of other lignin compounds. Graphical abstract: Image 1 Highlights: The transformation kinetics and mechanism of ozone with p -CMA were investigated. 2 . p -Hydroxybenzaldehyde is the most thermodynamically dominant product. The subsequent ozonolysis mechanisms of p -hydroxybenzaldehyde were elucidated. The reaction constant of p -CMA with ozone is 3.37 × 10 −16 cm 3 molecule −1 s −1 . Atmospheric implications of ozone on p -CMA cannot be ignored.